Harvard Business Review leader's handbook : make an impact, inspire your organization, and get to the next level - Ashkenas, Ronald N. (Harvard Business Review handbooks series., 2019)
ut aside all the hypey new frameworks, the listicles, the "10 best things you need" to succeed as a leader today. The critical leadership practices--the ones that will allow a leader to make the biggest impact over time--are already well established. They're about how you relate to others. How you make difficult strategic choices. How you get results. How you scan the landscape around you, build a vision for the future, and inspire people to follow you. In fact, these fundamental skills are becoming more important today as organizations and teams become increasingly networked and fragmented and the nature of leadership hierarchies changes. What's hard is actually doing these things--and excelling at them. In this book, strategy and change experts Ron Ashkenas and Brook Manville distill the best proven ideas and frameworks about leadership from Harvard Business Review and from their careers in leadership development and transformation into a concise handbook that shows rising leaders how to have the most impact on their organizations. You'll learn how to build a unifying vision, set strategy, manage for results, hire and inspire great leaders and teams, drive innovation, and, finally, lead yourself on your own career journey. Each chapter of the book describes one of these six practices in depth, discussing the pitfalls that real leaders face and how to overcome them, with insights from well-known leaders such as Stanley McChrystal, Dominic Barton, Darren Walker, Jack Welch, and Ann Mulcahy. Each chapter also synthesizes the best Harvard Business Review thinking on the topic. This book gives you the tools you need to have more impact as a leader today, and into the future.--